tính :
\(\left(\frac{1}{3}\right)^5\)\(\times\) 35
( 1,5 )3 . 8
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
ta có : ( -5/28 +7/4 + 8/35 ) : (- 69/20)
= ( -25/140 + 245/140 + 32/140 ) x (-20/69)
= (252/140) x (-20/69)
= (9/5) x (-20/69)
= (- 12/23)
tính nhanh:
2 x 3/7 + (2/9 - 10/7) - 5/3 x 9
= 6/7 + 2/9 - 10/7 - 5/3 x 9 = 6/7 + 2/9 - 10/7 - 15
= (6/7 - 10/7 ) + (2/9 - 135/9) = ( - 4/7 ) + (-133/9 )
= (- 36/63) + (-931/63)
= (- 967/63)
Bài 2 :
1) \(x-70=-45\) 2) \(\frac{4}{7}:x=\frac{12}{28}\)
\(\Rightarrow\) \(x=-45+70\) \(\Rightarrow x=\frac{4}{7}:\frac{12}{28}\)
\(\Rightarrow\) \(x=25\) \(\Rightarrow x=\frac{4}{3}\)
Vậy \(x=25\) Vậy \(x=\frac{4}{3}\)
3) Giống câu c) ở bài 1
4) \(x-50=-35\) 5) \(\frac{4}{7}.x=\frac{11}{18}\)
\(\Rightarrow x=-35+50\) \(\Rightarrow x=\frac{11}{28}:\frac{4}{7}\)
\(\Rightarrow x=15\) \(\Rightarrow x=\frac{77}{72}\)
Vậy \(x=15\) Vậy \(x=\frac{77}{72}\)
6) \(\left(\frac{2}{3}x+2,5\right):2\frac{2}{6}=6\)
\(\Rightarrow\)\(\left(\frac{2}{3}x+2,5\right):\frac{14}{6}=6\)
\(\Rightarrow\) \(\frac{2}{3}x+2,5=6.\frac{14}{6}\)
\(\Rightarrow\frac{2}{3}x+2,5=14\)
\(\Rightarrow\frac{2}{3}x=\frac{23}{2}\)
\(\Rightarrow x=\frac{23}{2}:\frac{2}{3}\)
\(\Rightarrow x=\frac{69}{4}\)
Vậy \(x=\frac{69}{4}\)
Bài 1:
1) \(\frac{7}{5}+\frac{-8}{5}=-\frac{1}{5}\)
2) \(-\frac{6}{5}.\frac{15}{24}=-\frac{3}{4}\)
3) \(\left(\frac{2}{3}+1,5\right)-3,5:7\frac{1}{2}=\)\(\frac{13}{6}-\frac{7}{15}=\frac{17}{10}\)
4) \(\frac{5}{8}-\frac{-7}{9}=\frac{5}{8}+\frac{7}{9}=\frac{101}{72}\)
5)\(\frac{-7}{3}.\frac{12}{28}=-1\)
a) \(\left(\frac{2}{5}-\frac{1}{2}\right)^2-\frac{11}{5}:\frac{-11}{5}=\left(-\frac{1}{10}\right)^2+1=1\frac{1}{100}\)
b) \(\left(-\frac{5}{7}\right)^2+8.\left(0,5\right)^2+\left(-1\right)^{2010}=\frac{25}{49}+2+1=3\frac{25}{49}\)
c) \(\frac{9999^2}{3333^2}+\left(0,5\right)^2.\left(-2\right)^4-\left(-\frac{4}{3}\right)^2=9+1-\frac{16}{9}=8\frac{2}{9}\)
d) \(\left|-\frac{2}{5}+\frac{1}{7}\right|:\frac{-3}{35}+\frac{-3}{7}.\frac{7}{5}=\frac{9}{35}.\frac{35}{-3}-\frac{3}{5}=-3\frac{3}{5}\)
e) \(\frac{1}{2}-\left(-0,4\right)+\frac{1}{3}+\frac{1}{5}-\frac{-1}{6}+\frac{-4}{35}+\frac{1}{41}\)
\(=\frac{1}{2}+\frac{2}{5}+\frac{1}{3}+\frac{1}{5}+\frac{1}{6}-\frac{4}{35}+\frac{1}{41}=1\frac{732}{1435}\)
A = (4+\(\frac{1}{5}\)) . \(\frac{18}{19}\)+ (2+\(\frac{8}{5}\)) . \(\frac{21}{5}\)
A= \(\frac{21}{5}\).18/19 + 18/5 . 21/5
A= 21/5 (18/19 + 18/5)
A= 21/5 . 432/95
A= 9288/95
b= 25/2. (3+2/7) - 23/7. (5 + 1/2)
b= 25/2 . 23/7 - 23/7 . 11/2
b= 23/7 (25/2 -11/2)
b=23/7 . 7
b= 23
\(\left(\frac{1}{3}\right)^5.3^5=\left(\frac{1}{3}.3\right)^3=1^5=1\)
\(\left(1,5\right)^3.8=\left(1,5\right)^3.2^3=\left(1,5.2\right)^3=3^3=27\)